2018
DOI: 10.7554/elife.31599
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar learning using perturbations

Abstract: The cerebellum aids the learning of fast, coordinated movements. According to current consensus, erroneously active parallel fibre synapses are depressed by complex spikes signalling movement errors. However, this theory cannot solve the credit assignment problem of processing a global movement evaluation into multiple cell-specific error signals. We identify a possible implementation of an algorithm solving this problem, whereby spontaneous complex spikes perturb ongoing movements, create eligibility traces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 132 publications
(187 reference statements)
1
43
0
Order By: Relevance
“…An earlier study (Bouvier et al . ) reported LTD induction by two CS separated by 100 ms. In those experiments, the first CS coincided with granule cell activity and was interpreted as a perturbation signal, whereas the second, delayed CS acts as an error signal, with an overall PF–CF stimulus duration lasting 100 ms, a pattern resembling classic PF–CF coactivation protocols.…”
Section: Discussionmentioning
confidence: 98%
“…An earlier study (Bouvier et al . ) reported LTD induction by two CS separated by 100 ms. In those experiments, the first CS coincided with granule cell activity and was interpreted as a perturbation signal, whereas the second, delayed CS acts as an error signal, with an overall PF–CF stimulus duration lasting 100 ms, a pattern resembling classic PF–CF coactivation protocols.…”
Section: Discussionmentioning
confidence: 98%
“…In a developmental context, the cerebellum may be actively engaged in refining and maintaining sensorimotor behaviors as the physiology of neural circuits, muscles, and sensory appendages matures. In the context of supervised cerebellar learning, classical theories predict that the coincident activation of a climbing fiber input and parallel fiber synapses drives long-term 1120 depression at the active parallel fiber to Purkinje cell synapses, leading to motor learning (Ito, 2001; but see Bouvier et al, 2018). Synaptic plasticity mechanisms both at other synapses and involving other cerebellar neurons (e.g.…”
Section: Complex Spike -Simple Spike Relationshipsmentioning
confidence: 99%
“…However, there are some notable exceptions (see Table 1, seventh column). Whereas some studies [83,88,89] suggest that LTD can only be induced in the absence of GABAergic inhibition, successful LTD induction has been reported without a block of GABAergic inhibition (Table 1, [4,60,82,112]). Some investigators have suggested that the study of LTD with inhibition blocked is “unphysiological”, however, another interpretation is that in vivo , the induction of LTD requires a transient reduction in the level of inhibitory input to the Purkinje cell from the molecular layer interneurons.…”
Section: Biologically Plausible Variations That May Influence the Indmentioning
confidence: 99%
“…The synaptic physiologist must make many choices, as outlined above. There have been attempts to make choices that recreate some of the specific conditions that are present in vivo [52,68,112]. However, our lack of knowledge about what exactly these conditions are during learning remains a challenge.…”
Section: Implications For Future Researchmentioning
confidence: 99%